2013
DOI: 10.3109/13693786.2012.686673
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicansand non-Candida albicansfungemia in an institutional hospital during a decade

Abstract: Since the outcomes of patients with candidemia is poor and Candida spp. with increased resistance to antifungal therapy may be associated with these results, the emergence of these blood infections caused by non-C. albicans Candida spp. was explored prospectively over a two-year period (2009-2010). Candidemia was defined as the recovery of Candida spp. in culture from a patient's blood sample. The in vitro susceptibility of each isolate to amphotericin B, caspofungin, fluconazole and voriconazole was determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 20 publications
0
31
1
Order By: Relevance
“…Of note, our study showed that presence of sepsis symptoms was predominant in patients infected with C. albicans (88.9%), C. tropicalis (94.4%), C. guilliermondii (85.7%) and C. sake (83.3%) rather than in patients infected by other Candida species (44.4%-60.0%). Interestingly, we observed in the present study that C. guilliermondii and C. sake represented 5.8% and 5.0% of the isolates; while only 0.2%-2.4% of C. guilliermondii was observed in European countries [11,18,41,42], in Taiwan [43] and in Latin America except in Honduras (20%) [33]. The emergence of severe sepsis due to C. sake is here remarkable, knowing that the latter species represented only 0.03% of isolates in a recent publication from ARTEMIS [44].…”
Section: Discussionmentioning
confidence: 63%
“…Of note, our study showed that presence of sepsis symptoms was predominant in patients infected with C. albicans (88.9%), C. tropicalis (94.4%), C. guilliermondii (85.7%) and C. sake (83.3%) rather than in patients infected by other Candida species (44.4%-60.0%). Interestingly, we observed in the present study that C. guilliermondii and C. sake represented 5.8% and 5.0% of the isolates; while only 0.2%-2.4% of C. guilliermondii was observed in European countries [11,18,41,42], in Taiwan [43] and in Latin America except in Honduras (20%) [33]. The emergence of severe sepsis due to C. sake is here remarkable, knowing that the latter species represented only 0.03% of isolates in a recent publication from ARTEMIS [44].…”
Section: Discussionmentioning
confidence: 63%
“…Colonization and infection follow a seasonal distribution, with higher rates during the warm months of the year. Our understanding of the epidemiology of C. kefyr has been limited, derived mainly from case reports (12,27,28), laboratorybased analyses (13)(14)(15)(29)(30)(31)(32)(33)(34), and large surveillance registries (11). This body of evidence has suggested that HM patients may be a high-risk group for infection with this organism, albeit C. kefyr is a rare cause of invasive disease.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the surveillance of the susceptibility to echinocandin of this relatively scarce species, responsible for Ͻ1% to 1.6% of cases of candidemia (13,14), may be of interest. Awaiting other reports of such rapid resistance emergence, we suggest closer monitoring of C. kefyr in patients treated with echinocandins.…”
mentioning
confidence: 99%